Choosey journalists choose GIFs - Gil, Jodie Mozdzer (The Quill, 2016)
The still photographs incorporate subtle movement, such as wind blowing grass or eyes blinking, that play on repeat through an animated GIF. [...]don't make your readers seasick with too much movement or too many GIFs on the same page.t
Keywords: Digital broadcasting; Photographs; School districts; Software reviews; Video recordings; dept.jrn

The Power of Free Expression in America - Harris, Frank (Cognella Academic Publishing, 2016)
Keywords: Freedom of expression; United States; dept.jrn; faculty_collection

The Craft of Quoting: The Art of Writing It Like It's Said - Harris, Frank (Cognella, Inc., 2016)
The Craft of Quoting helps student-writers develop the ability to use quotes in such a way that their readers "hear" and "feel" what the speaker is saying and understand its relevance to the topic at hand. Students will learn how to write quotes with style, clarity, and consistency. The book provides clear guidelines for mechanical correctness, appropriate attribution, and paraphrasing. The use of paragraph breaks for stylistic purposes is also addressed. In addition, The Craft of Quoting sets out twelve "quote-nots" that help students avoid the common pitfalls of using quotes in written work, as well as nine essential quote patterns that enhance efficacy and impact. The Craft of Quoting also addresses the importance of ethics in writing, especially as these relate to plagiarism and academic dishonesty. Practical and concise, The Craft of Quoting is ideally suited to journalism students whose reporting involves interviewing sources. It is also an excellent tool for second-tier writing classes in which students explore other people's thoughts and feelings in their work.
Keywords: Handbooks, manuals, etc; Journalism; dept.jrn; faculty_collection